Разработка буровых коронок армированных алмазами АРК-4 - Бугаков, В.И.; Поздняков, А.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Rational designs of prospecting drilling bits КСК were developed and experimental batches
of bits were made at high pressures (1,5 GPa and temperature 1050 ?С). Bench tests of the developed
bits КСК reinforced by diamonds АРК-4, have shown high operational characteristics at
drilling of rocks VIII-IX categories of drillability. The design procedure of an optimum design of
drilling bits КСК depending on parameters of drilling and the size of grain АРК-4 for rocks VIII-IX
categories of drillability is offered.